2018
DOI: 10.34152/fe.13.2.144-162
|View full text |Cite
|
Sign up to set email alerts
|

REKAYASA MODEL PENGUATAN KESIAPAN KERJA LULUSAN PENDIDIKAN VOKASI (Studi pada SMK di Kota Semarang)

Abstract: The study of job readiness has been widely researched but is still an interesting topic given the empirical phenomenon which indicates the low level of work readiness. In addition, the findings from the studies that have been conducted on explanatory variables of work readiness are also not conclusive. Departing from this phenomenon, the study again developed a research model that "mated" the empirical and theoretical aspects that could explain the variable work readiness. Empirical testing on the work readine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This finding shows that if the respondent has strong self efficacy, it will increase the work readiness of the respondent. Studies of Stevani & Yulhendri (2014), Trisnawati (2013), Eliyani, Yanto & Sunarto (2016 and Noviana (2014), (Sijabat, 2018) on these two variables indicated that self efficacy had a significant positive effect on work readi-ness.…”
Section: Effect Of Self-efficacy On Work Readinessmentioning
confidence: 96%
See 3 more Smart Citations
“…This finding shows that if the respondent has strong self efficacy, it will increase the work readiness of the respondent. Studies of Stevani & Yulhendri (2014), Trisnawati (2013), Eliyani, Yanto & Sunarto (2016 and Noviana (2014), (Sijabat, 2018) on these two variables indicated that self efficacy had a significant positive effect on work readi-ness.…”
Section: Effect Of Self-efficacy On Work Readinessmentioning
confidence: 96%
“…This finding shows that if the respondent has a strong locus of control, it will increase the work readiness of the respondent. In the Muyasaroh study, Hana Binti., Ngadiman & Nurhasan Hamidi (2013), (Sijabat, 2018) showed that the Locus of control had a significant positive effect on work readiness. Likewise, the Primary study, Beny Dwi & Suharnan (2014) also showed the same results.…”
Section: Effect Of Locus Of Control On Work Readinessmentioning
confidence: 99%
See 2 more Smart Citations